2008
DOI: 10.2460/javma.233.7.1089
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of perinuclear anti-neutrophilic cytoplasmic autoantibodies as an early marker of protein-losing enteropathy and protein-losing nephropathy in Soft Coated Wheaten Terriers

Abstract: This article is an open access article distributed under the terms and conditions of the Creative Commons Attribution (CC BY) license (https:// creativecommons.org/licenses/by/ 4.0/).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
17
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(18 citation statements)
references
References 7 publications
0
17
1
Order By: Relevance
“…However, pANCA seropositivity is not specific for CIE and also can occur with other immune-mediated, infectious, or neoplastic diseases 101,102. Positivity for pANCA is associated with PLE, protein-losing nephropathy, or both in Soft Coated Wheaten Terriers, with pANCA positivity being detected >2 years before the onset of hypoalbuminemia 103. Although pANCA is a difficult assay to acquire, it might be useful for diagnosing dogs with FRE and for early detection of protein-losing disease in Soft Coated Wheaten Terriers (where fecal α 1 PI also might predict gastrointestinal protein loss before the development of hypoalbuminemia).…”
mentioning
confidence: 99%
“…However, pANCA seropositivity is not specific for CIE and also can occur with other immune-mediated, infectious, or neoplastic diseases 101,102. Positivity for pANCA is associated with PLE, protein-losing nephropathy, or both in Soft Coated Wheaten Terriers, with pANCA positivity being detected >2 years before the onset of hypoalbuminemia 103. Although pANCA is a difficult assay to acquire, it might be useful for diagnosing dogs with FRE and for early detection of protein-losing disease in Soft Coated Wheaten Terriers (where fecal α 1 PI also might predict gastrointestinal protein loss before the development of hypoalbuminemia).…”
mentioning
confidence: 99%
“…Details regarding these 38 patients can be found in a previously reported study. 5 Agreement between the two methods was assessed by testing a subset of 10 samples by the same person (KA), using both assays.…”
Section: Patient Selectionmentioning
confidence: 99%
“…10 Studies involving a cohort of softcoated wheaten terriers (SCWT) and SCWT-beagle crossbred dogs with PLN/PLE indicated that antibodies appeared up to 2 years before development of clinically relevant disease, suggesting possible use of ANCA to predict onset of disease. 5 Titers for ANCA remained positive once identified. These various studies suggest that ANCA testing could be utilized for a number of immune-mediated disease syndromes although an assay designed for dogs is not currently widely available.…”
mentioning
confidence: 97%
See 2 more Smart Citations